2015
DOI: 10.1523/jneurosci.3214-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Losing the Music: Aging Affects the Perception and Subcortical Neural Representation of Musical Harmony

Abstract: When two musical notes with simple frequency ratios are played simultaneously, the resulting musical chord is pleasing and evokes a sense of resolution or "consonance". Complex frequency ratios, on the other hand, evoke feelings of tension or "dissonance". Consonance and dissonance form the basis of harmony, a central component of Western music. In earlier work, we provided evidence that consonance perception is based on neural temporal coding in the brainstem (Bones et al., 2014). Here, we show that for liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
3
22
1
Order By: Relevance
“…However, a careful inspection of the existing literature on the effects of aging on neural representations of simple and complex stimuli provides some arguments that might explain these inconsistent findings. Bones and Plack (2015) found a decline in brainstem temporal representation of complex stimuli (musical dyads) with increasing age. However, while the audiometric thresholds in the young and aged participants in this study were within normal limits between 250–2000 Hz, the hearing threshold at audiometric frequencies higher than 2000 Hz in either group were not taken into consideration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a careful inspection of the existing literature on the effects of aging on neural representations of simple and complex stimuli provides some arguments that might explain these inconsistent findings. Bones and Plack (2015) found a decline in brainstem temporal representation of complex stimuli (musical dyads) with increasing age. However, while the audiometric thresholds in the young and aged participants in this study were within normal limits between 250–2000 Hz, the hearing threshold at audiometric frequencies higher than 2000 Hz in either group were not taken into consideration.…”
Section: Discussionmentioning
confidence: 98%
“…Based on an analysis of covariance with age as a covariate, our results showed that hearing loss to be the main contributor to the observed degradation in neural representation of both envelope and TFS, with age not contributing significantly. The majority of recent studies examining the effects of age on the brainstem FFR (Clinard et al 2010; Marmel et al 2013; Bones & Plack 2015) suggest that brainstem neural representation of temporal cues undergoes some degradation with advancing age. At first glance, the results from the current study appear to be inconsistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, for the Pythagoreans, the numerical 1:2 relationship of an octave jump was even more significant than 4:5:6, since the numbers 1 and 2 are “simpler” than 4, 5, and 6, and accordingly, the octave chord is more consonant. (This “mysticism of numbers” has a scientific explanation based on the psychophysical response of the human brain to the interference of the respective higher harmonics resulting in pleasant beats: see ).…”
Section: Theoretical Basis: Frequency Ratios In the Musical Scale Of mentioning
confidence: 99%
“…The scalp-recorded brainstem frequency-following response (FFR) is a sustained “neurophonic” potential with putative generators in the rostral brainstem [ 15 , 16 ] which reflects spectrotemporal properties of the eliciting acoustic stimulus. Previous studies demonstrated that NPS measured from FFRs correlates with behavioral reports of consonance and dissonance [ 8 , 17 19 ]. With the initial idea of maximizing FFR responses, these studies used synthetic tones with specific (but artificial) spectra (complex tones with 5–6 equal amplitude partials of a harmonics series).…”
Section: Introductionmentioning
confidence: 99%